Mejora continua aplicada a las técnicas y procedimientos de la fundición de placas de aluminio en alúmina S.A. (2014)
In this project the mold change process for the preparation of aluminum plates is performed with reference to the new technology implemented by Wagstaff Industries around the world who have implemented technology adjustable cast ingots in countries like Brazil , China, Netherlands, Russia, Australia , South America , Taiwan, United Kingdom, Germany , Croatia , Canada and the U.S., this technology platform for setting iron molds are used and to have 87 different sizes that can be used as variables molds reducing the number of sets of parts to produce a range of sizes of rolled bars or plates . All this in order to develop a high quality in the plates recovered and increased. The plates or ingots produced by this technology has a minimum of curvature at the end surfaces leading to higher and high recovery rates. The high quality of these ingots using this technology generates significant savings and cut operating activities. Given the above and taking into account the issues presented Alumina in terms of increased operating activities due to the use of fixed molds and presents a decrease in recovered, the latter being the indicator by which the process is measured according to the global standard and identifies the loss or gain of the process technology is implemented in the company and thus reflect improvements in the production process.